2021
DOI: 10.1037/aca0000348
|View full text |Cite
|
Sign up to set email alerts
|

The Aesthetic Responsiveness Assessment (AReA): A screening tool to assess individual differences in responsiveness to art in English and German.

Abstract: The version presented here may differ from the published, performed or presented work. Please go to the persistent GRO record above for more information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 70 publications
8
73
0
Order By: Relevance
“…1 was conducted in English at New York University in New York, NY. At the start of the experiment, each participant completed a set of questionnaires: a demographic background questionnaire, an abbreviated version of the Positive and Negative Affect Schedule (PANAS-X; Watson & Clark, 1999), the State-Trait Anxiety Inventory (STAI-Y; Grös et al, 2007;Julian, 2011;Spielberger, 1983), and the Aesthetic Responsiveness and Engagement Assessment (AReA; Schlotz et al, 2020), in their English version using pen and paper. The AReA questionnaire is a tool developed by our group to measure participants' general aesthetic responsiveness with items assessing the frequency with which people experience three relevant states: aesthetic appreciation, intense aesthetic experiences, and creative engagement.…”
Section: Methodsmentioning
confidence: 99%
“…1 was conducted in English at New York University in New York, NY. At the start of the experiment, each participant completed a set of questionnaires: a demographic background questionnaire, an abbreviated version of the Positive and Negative Affect Schedule (PANAS-X; Watson & Clark, 1999), the State-Trait Anxiety Inventory (STAI-Y; Grös et al, 2007;Julian, 2011;Spielberger, 1983), and the Aesthetic Responsiveness and Engagement Assessment (AReA; Schlotz et al, 2020), in their English version using pen and paper. The AReA questionnaire is a tool developed by our group to measure participants' general aesthetic responsiveness with items assessing the frequency with which people experience three relevant states: aesthetic appreciation, intense aesthetic experiences, and creative engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing upon previous findings (Diessner, 2019;Diessner et al, 2008;Schlotz et al, 2020;Zabihian & Diessner, 2016), we investigated the relationship between savoring art and well-being in a sample of nonartists and nonclinical adults. Consistent with our hypothesis, the results suggested that savoring art is associated with a greater level of both SWB and PWB (Study 1).…”
Section: Discussionmentioning
confidence: 98%
“…Empirical aesthetics is concerned with how incoming sensory, emotional or social stimuli (e.g., a painting, a piece of music, the sight of a person, etc.) acquire value for the individual (e.g., makes an individual "like" or "dislike" the stimulus), particularly when that value is based on the structure of the stimulus itself, rather than on any associated rewards (Vessel, 2020). In addition, empirical aesthetics is also concerned with how this value assignment affects subsequent behavior and decision-making of the individual in relation to the cue (e.g., a decision to purchase a painting, or not, visit a museum or a concert over and again, or never return, attend a music class, or not, etc.).…”
Section: The Aesthetic Responsiveness Assessment (Area) In Persian La...mentioning
confidence: 99%
“…The present paper presents a scale validation of the Aesthetic Responsiveness Assessment (AReA; Schlotz et al, 2020) in a new language, and adapted to a new culture. The AReA is, a short 14-item questionnaire to assess individual differences in responsiveness to aesthetic stimuli (e.g., aesthetic responsiveness to visual art, dance, music, film, and poetry).…”
Section: The Aesthetic Responsiveness Assessment (Area) In Persian La...mentioning
confidence: 99%